Holding Talent Back? : What is next for the future of Level 3? : With a Foreword from David Willetts - (:unkn) unknown (My University, 2022)
"In this collection, different experts from a range of backgrounds consider the current plan to defund many BTECs [Business and Technology Education Council awards] and other popular Level 3 Applied General qualifications. Together, the chapters argue this could close off a useful and proven route for students from a wide range of backgrounds, including for those hoping to reach higher education. While the new T Levels have still to prove themselves, the authors recognise their potential while also arguing that their success does not have to rest on shutting off popular existing tried- and-tested options." (Editor, BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; 370; Berufsbildung; Hochschulbildung; Durchlässigkeit im Bildungssystem; Berufsbildungspolitik; Bildungsreform; Großbritannien